In-situ Studies of High Temperature Thermal Batteries: A Perspective - Payne, Julia L.; Giagloglou, Kyriakos; Carins, George M.; Crouch, Christina J.; Percival, Julia D.; Smith, Ronald I.; Gover, Richard K. B.; Irvine, John T. S. (Frontiers in Energy Research, 2018)
Here we present a perspective on in-situ studies of high temperature batteries. We focus on a primary battery technology- the thermal battery- which possesses a molten salt electrolyte. We discuss aspects of sample environment design, data collection and will briefly look at some case studies. We aim to highlight the importance of using in-situ techniques in studying electrochemical devices such as high temperature batteries.